Model Komunikasi dalam Penanggulangan Bencana Kebakaran Hutan dan Lahan oleh Badan Penanggulangan Bencana Daerah Kabupaten Bintan - Ananda, Almar; Poti, Jamhur; Hendrayady, Agus (PUBLICNESS: Journal of Public Administration Studies, 2024)
The purpose of this research is to find out the communication model and inhibiting factors in forest and land fire disaster management by the Regional Disaster Management Agency of Bintan Regency. This research uses a qualitative approach with descriptive research type. The data collection techniques used are observation, interviews, and documentation. Based on the results of research using the Wilbur Schramm Communication Model theory, it shows that (1) In the source indicator, the messenger has communicated such as Schools, Communities, Villages, RT / RW, Bhabinkamtibmas and Babinsa. However, in its implementation, the source of the messenger still does not understand the mechanism for reporting forest and land fire disaster events. (2) In the message indicator, it is characterized by reports of forest and land fire disasters delivered through Whatsapp, Instagram and Mass Media. However, the messages conveyed are not always complete, accurate and precise. (3) In the target indicator, there are still obstacles in communication and lack of trust in receiving reports of forest and land fire disasters. The conclusion in this research is that the two-way communication model used is already running. However, the two-way communication carried out still has obstacles because there is no Standard Operating Procedure (SOP) for communication of forest and land fire disaster management in accordance with the Bintan Regency area.